'I don't think this woman had anyone in her life': Loneliness and singlehood in Six Feet Under. Issue 4 (November 2018) - Yodovich, Neta; Lahad, Kinneret
This article offers a critical analysis of representations of loneliness and singlehood, embodied in the narrative of the 'old maid's' lonely death. The study contributes to a complex understanding of single women and the resignification of emotions conventionally ascribed to this category. By bridging the gap between two rarely linked bodies of knowledge – singlehood and the sociology of emotions – the authors do not ask what loneliness is, but, following Sara Ahmed's work, rather what loneliness does . To this end, this article employs a content analysis of versatile media texts, focusing on the acclaimed television series Six Feet Under, a polysemic text which juxtaposes both conservative and subversive meanings. The study contributes both to the vibrant discussion of social emotions as well as to the existing critical scholarship about singlehood, and seeks to challenge the limited set of representations attached to single women, and hegemonic ideals of family and solitary life.